Occupational low back pain prevention capacity of nurses in China: A multicenter cross-sectional study - Liu, Qianru; Liu, Xue; Lin, Huijing; Sun, Yu; Geng, Li; Lyu, Yongli; Wang, Mengna (Frontiers in Public Health, 2023)
Introduction Nurses have a high prevalence of occupational low back pain, especially since the outbreak of the COVID-19 pandemic, which has increased the nurses' workloads. It has brought a huge burden on nurses and their professional development. Nurses' occupational low back pain prevention capacity is the logical starting point and core of interventions to prevent its occurrence. To date, there is no study investigating it with a scientific scale. Therefore, a multicenter cross-sectional study was conducted to explore the current status of nurses' capacity in occupational low back pain prevention and its influencing factors in China. Methods Using a two-stage, purposive and convenience mixed sampling method, 1331 nurses from 8 hospitals across 5 provinces (Hubei, Zhejiang, Shandong, Henan, and Sichuan) in the southern, western, northern, and central areas of mainland China were involved in this study. The demographic questionnaire and occupational low back pain prevention behavior questionnaire were used for data collection. The descriptive analysis, univariate analysis, and multiple stepwise linear regression were used for data analysis. Results The results showed that the occupational low back pain prevention behavior questionnaire score was 89.00 (80.00, 103.00) [M (Q1, Q3)], which indicated that nurses' ability was at a moderate level. Participation in prevention training before, perceived stress at work, and working hours per week were predictors for nurses' occupational low back pain prevention capacity. Discussion To improve nurses' prevention ability, nursing managers should organize various training programs, strengthen regulations to reduce nurses' workload and stress, provide a healthy workplace, and offer incentives to motivate nurses.